Molecular, Biological, and In Vivo Characterization of the Guinea Pig Cytomegalovirus (CMV) Homologs of the Human CMV Matrix Proteins pp71 (UL82) and pp65 (UL83) - McGregor, Alistair (American Society for Microbiology, 2004)
We recently identified the genes encoding the guinea pig cytomegalovirus (GPCMV) homologs of the upper and lower matrix proteins of human CMV, pp71 (UL82) and pp65 (UL83), which we designated GP82 and GP83, respectively. Transient-expression studies with a GP82 plasmid demonstrated that the encoded protein targets the nucleus and that the infectivity and plaquing efficiency of cotransfected GPCMV viral DNA was enhanced by GP82. The transactivation function of GP82 was not limited to GPCMV, but was also observed for a heterologous virus, herpes simplex virus type 1 (HSV-1). This was confirmed by its ability to complement the growth of an HSV-1 VP16 transactivation-defective mutant virus in an HSV viral DNA cotransfection assay. Study of a GP82 “knockout” virus (and its attendant rescuant), generated on a GPCMV bacterial artificial chromosome construct, confirmed the essential nature of the gene. Conventional homologous recombination was used to generate a GP83 mutant to examine the role of GP83 in the viral life cycle. Comparison of the one-step growth kinetics of the GP83 mutant (vAM409) and wild-type GPCMV indicated that GP83 protein is not required for viral replication in tissue culture. The role of GP83 in vivo was examined by comparing the pathogenesis of wild-type GPCMV, vAM409, and a control virus, vAM403, in guinea pigs. The vAM409 mutant was significantly attenuated for dissemination in immunocompromised strain 2 guinea pigs, suggesting that the GP83 protein is essential for full pathogenicity in vivo.